WICKED insights into the role of green leases - Patrick, J; Bright, S (Sweet and Maxwell, 2016)
Examines the research findings of the WICKED project, based at the University of Oxford, exploring the impact of "green lease" clauses on the energy performance of commercial property in the retail sector. Outlines the regulatory context of the green lease initiative. Assesses how the landlord-tenant relationship and split incentives affect the uptake of green leases for retail units. Considers the types of green clause in the leases under study.